Public realm : reviving Kajang Town Centre towards the liveable environment - Nor Azami, Nor Hidayah (2018)
The study is conducted in the means of understanding of the public realm that can give a liveable environment to the town. This is because public realm can influence the form of the town and the daily interaction will take place at the community level. When the town is being developed, sometimes it makes the town loss its identity and lack of green area as a place to socialize. So it's important to provide a successful public realm in a town. In addition, this study will also identify the issues in the town of Kajang and will then provide a guideline to the town to resolve issues that exist. Among the issues in the town are road division, water pollution, and do not have a comfortable place to socialize. Furthermore, in this study also provides some approaches to solving these issues. Among the approaches used to solve this issue is to provide community parks for local communities and visitors. The riparian plant has also been used to restore the contaminated river water. The preservation of heritage buildings in the town is also necessary as it has its own historical value. As the result, it is a concise that thoroughly satisfies human needs while protecting the environment. The overlaying map that has been used will identify potential areas for the public realm and provide the comforts of pedestrians. However, it requires involvement from all parties in order to provide a successful public realm in the town of Kajang.